THE NEED FOR AN ACTIVITY CENTERED SCIENCE PROGRAM. - Norton, Jerry L. (Science Education, 1963)
The article specifies the need for an activity-centered science program for elementary science education in the United States. Apparently, existing general science programs have become a superficial smattering of unarticulated topics, that is, it has become too general. One of the basic advantages of the doing approach or activity-centered program is its variety for individual differences of ability. More significantly, the guided activities permit tangible evidence of difficult abstractions, leading to increased comprehension and physical evidence.